Brincando para continuar a ser criança e libertar-se do confinamento por estar hospitalizada e em precaução - Depianti, Jessica Renata Bastos [UNIFESP] (2017)
Hospitalization, by itself, is a triggering factor for stress and distress for the child, since she is detached from her habitual routine. This situation is worsened when she is a precautionary condition, which deprives her of freedom and of being able to interact with other hospitalized children. The possibility of playing has been recommended to reduce the stress arising from the hospitalization. Thus, this study was intended to understand the meaning of playing for the hospitalized child and in precaution. This is a qualitative research that used the Symbolic Interactionism as its theoretical benchmark. It was performed in a public children’s hospital in the city of São Paulo, with eight children aged between five and ten years, hospitalized in private and precautionary rooms. It´s project was approved by the Research Ethics Committee of UNIFESP under opinion nº 1.267.939/2015, and all ethical procedures were respected. The data collection occurred between April and September 2016 and was accomplished by means of participant observation, with the elaboration of a field diary, based on a playful interaction developed with the child during three consecutive days, and by means of a semi-structured interview mediated by the Story-Drawing Procedure with Theme. The data were analyzed by means of Qualitative Content Analysis by following the steps of codification, categorization, integration and description of the unveiled categories. The results revealed that, when playing, the child perceives herself as an active subject in the hospitalization process, having voice and placing herself as the main actor that can decide and dominate a situation; expresses her dreams and desires, including the desire to get rid of the confinement. They also showed that, during the three days of the playful activity, there was an evolution of the interactions of the child with the environment, with the researcher and with herself, thereby becoming calmer, quiet and happy, besides perceiving herself as a respected person. Furthermore, they highlighted that the child defines the hospital as a place of distress, restrictions and procedures, and nursing professionals as the only people who perform them; unveiled the importance and the benefits of taking part in a captivating playful activity, with an adult who is available to play, and the strategies developed by the child to take part in this activity, despite the difficulties and limitations that she has. One should emphasize that, as a defender of children’s rights, the nursing professional must engage in the promotion of the playful activity, incorporating it into his health care practice, aiming to establish the bond and to facilitate the performance of care actions, demystifying the image of the nurse as the professional who only performs procedures, enabling the expression of the child, making the hospitalization a less traumatic event and allowing her to continue being a child and to achieve the ability to get rid of the confinement for being hospitalized and in precaution.